Historical research on the practices of care and assistance in witchcraft trials held at Poschiavo (CH) between 1631 and 1753 - Giorgetta, Stefano; Manzoni, Edoardo; Lusignani, Maura (Medicina Historica, 2023)
The context of Val Poschiavo has shown to be the location of numerous trials against witches in the post-Tridentine period, recognised to be a crucial era for the history of medicine and for the history of assistance, inevitably linked to the history of nursing care. Assistance is to be looked for, in this period, in the domestic settings of the population’s life, in which women exerted their caring practice.The purpose of the research is to highlights the link between the witch hunting period in the context of Val Poschiavo and the history of assistance, comparing gestures of assistance and care of women accused of witchcraft to the modern-day basic nursing care.The trial records of 51 women accused of witchcraft between 1631 and 1753 are examined and analysed using the historical research methodology.Overall, 111 gestures have emerged. These were divided in gestures of care (n=51) and gestures of assistance (n=60), expressed through feeding, touch, physical proximity, words, knowledge/competence, the look and the usage of herbs.The results allow to relate some women accused of witchcraft to caring women and offer useful groundwork to wonder about the meaning of nursing actions, with an explicit reference to the Fundamentals of Care, expression of a memory maybe forgotten, but humanly essential and indispensable.